Roux-en-Y gastric bypass surgery reprograms enterocyte triglyceride metabolism and postprandial secretion in rats - Sharon Kaufman; Myrtha Arnold; Abdiel Alvarado Diaz; Heike Neubauer; Susanne Wolfrum; Harald Köfeler; Wolfgang Langhans; Jean-Philippe Krieger (Elsevier, 2019)
Objective: Roux-en-Y gastric bypass (RYGB) surgery produces rapid and persistent reductions in plasma triglyceride (TG) levels associated with fewer cardiovascular events. The mechanisms of the reduction in systemic TG levels remain unclear. We hypothesized that RYGB reduces intestinal TG secretion via altered enterocyte lipid handling. Methods: RYGB or Sham surgery was performed in diet-induced obese, insulin-resistant male Sprague-Dawley rats. First, we tested whether RYGB reduced test meal-induced TG levels in the intestinal lymph, a direct readout of enterocyte lipid secretion. Second, we examined whether RYGB modified TG enterocyte secretion at the single lipid level and in comparison to other lipid subclasses, applying mass spectrometry lipidomics to the intestinal lymph of RYGB and Sham rats (0-21 days after surgery). Third, we explored whether RYGB modulated the metabolic characteristics of primary enterocytes using transcriptional and functional assays relevant to TG absorption, reesterification, storage in lipid droplets, and oxidation. Results: RYGB reduced overall postprandial TG concentrations compared to Sham surgery in plasma and intestinal lymph similarly. RYGB reduced lymphatic TG concentrations more than other lipid subclasses, and shifted the remaining TG pool towards long-chain, unsaturated species. In enterocytes of fasted RYGB rats, lipid uptake was transcriptionally (Fatp4, Fabp2, Cd36) and functionally reduced compared to Sham, whereas TG reesterification genes were upregulated. Conclusion: Our results show that RYGB substantially reduces intestinal TG secretion and modifies enterocyte lipid absorption and handling in rats. These changes likely contribute to the improvements in the plasma TG profile observed after RYGB in humans. Keywords: RYGB, Intestinal lymph, Enterocyte metabolism, Dyslipidemia, Obesity